KAJIAN ALOKASI ANGGARAN BIAYA JARINGAN IRIGASI BERBASIS KINERJA IRIGASI DAN NILAI MANFAAT EKONOMI (STUDI KASUS D.I. PRAMBATAN KOTA BATU) - Kesuma, Alex Wahyu; Trijuwono, Pitojo; Sayekti, Rini Wahyu (Fakultas Teknik, Universitas Brawijaya, 2012)
There are many factors that determined budget allocation in irrigation network: technical factor, policy, political factor, and local economic capacity to fund an activity.Budget allocation design is conducted by consider priority index factor and budget allocation index based on Budget (RAB) nominal value, irrigation network performance, economic benefit of agricultural activities, and land area of the irrigation network. With Analysis of priority index = 0,05(IRAB) + 0,8(1/IKSI) + 0,1(IME) + 0,05(ILBS), resulted that maintenance activities of JI Prambatan Kanan is the first priority with priority index value 1,334, and JI Prambatan Kiri is second priority with priority index value 1,315. Nominal value of the budget and budgetary plafond for annually costs of irrigation network is considered in the process of allocating budget to the maintenance activities.Keywords: Use value, irrigation, performance